Optimal treatment for spermatogenesis in male patients with hypogonadotropic hypogonadism. Issue 31 (August 2019) - Lin, Jianli; Mao, Jiangfeng; Wang, Xi; Ma, Wanlu; Hao, Ming; Wu, Xueyan
Abstract: Background: To compare the efficacies of gonadotropin-releasing hormone (GnRH) pulse subcutaneous infusion with combined human chorionic gonadotropin and human menopausal gonadotropin (HCG/HMG) intramuscular injection have been performed to treat male hypogonadotropic hypogonadism (HH) spermatogenesis. Methods: In total, 220 idiopathic/isolated HH patients were divided into the GnRH pulse therapy and HCG/HMG combined treatment groups (n = 103 and n = 117, respectively). The luteinizing hormone and follicle-stimulating hormone levels were monitored in the groups for the 1st week and monthly, as were the serum total testosterone level, testicular volume and spermatogenesis rate in monthly follow-up sessions. Results: In the GnRH group and HCG/HMG group, the testosterone level and testicular volume at the 6-month follow-up session were significantly higher than were those before treatment. There were 62 patients (62/117, 52.99%) in the GnRH group and 26 patients in the HCG/HMG (26/103, 25.24%) group who produced sperm following treatment. The GnRH group (6.2 ± 3.8 months) had a shorter sperm initial time than did the HCG/HMG group (10.9 ± 3.5 months). The testosterone levels in the GnRH and HCG/HMG groups were 9.8 ± 3.3 nmol/L and 14.8 ± 8.8 nmol/L, respectively. Conclusion: The GnRH pulse subcutaneous infusion successfully treated male patients with HH, leading to earlier sperm production than that in the HCG/HMG-treated patients. GnRH pulse subcutaneous infusion is a preferred method.